Effect of Multisensory Method Starters Against Reading Ability in Children Aged 4-5 Years in kindergarten Baitul Hikmah Pekanbaru - Rezeki Irma Suryani; Zulkifli N Zulkifli N; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract this research is motivated by the low reading ability of children in the beginning. The high number of starters who can not read will result in the child having difficulty in participating in learning activities. So can result in a child's difficult to capture and understand information presented in a variety of textbooks, books and materials supporting learning resources written another. The purpose of this study was to determine the extent to which the influence of multisensory method on beginning reading skills in children at the kindergarten. This study used a quantitative approach and the type of research is quasi-experimental. The subjects were children aged 4-5 years, amounting to 23 children consisting of 9 boys and 14 girls, with as many details of the treatment group and a control group of 12 people 11 people from the research and discussion is known that the value ttabel 2.07 and the value of t is 14.22. Thus the value of t is greater than t table, it indicates that there are significant multisensory method on beginning reading skills of children. This means that the hypothesis Ha is accepted, ie there is a significant effect of multisensory method to beginning reading skills in children aged 4-5 years in kindergarten Baitul Hikmah Pekanbaru. Keywords: Multisensory Method, Starters Reading Ability